Effectiveness of Eye Movement Desensitization and Reprocessing-EMDR Method in Patients with Chronic Subjective Tinnitus - Fatih Bal; Muzaffer Kırış (Brain Sciences)
This research aimed to investigate the effectiveness of the Eye Movement Desensitization and Reprocessing (EMDR) method on chronic subjective tinnitus. The research was planned as an observational study. The study group comprises individuals who applied to the training and research hospital in Ankara between 2019 and 2020 and were aged between 15 and 60 years old. They were identified as having tinnitus. The study samples were determined as 36 participants selected through purposeful sampling. The samples of the 36 participants included in the study. 12 were assigned to the 1st Group EMDR and Masking Group, 12 to the 2nd Group Masking and EMDR Group, and 12 to the 3rd Control Group. The study’s dependent variable was the tinnitus levels of the participants, and the independent variable was EMDR and the Masking method. The dependent variable data of the study was collected with the Visual Analog Scale and Tinnitus Handicap Inventory (THI). EMDR and Masking methods used as independent variables in the study were conducted in eight sessions for two months. As a result of the Wilcoxon Sign test used to determine whether the EMDR Method is effective on tinnitus severity level, the difference between tinnitus severity level pretest and post-test median scores of tinnitus patients was found to be statistically significant. Our research findings show that the EMDR method reduces and improves chronic subjective tinnitus, and further studies with a larger sample size could confirm our results.